Computation of Ice Shedding Trajectories Using Cartesian Grids, Penalization, and Level Sets. (16th March 2011) - Beaugendre, Héloïse; Morency, François; Gallizio, Federico; Laurens, Sophie
Abstract : We propose to model ice shedding trajectories by an innovative paradigm that is based on cartesian grids, penalization and level sets. The use of cartesian grids bypasses the meshing issue, and penalization is an efficient alternative to explicitly impose boundary conditions so that the body-fitted meshes can be avoided, making multifluid/multiphysics flows easy to set up and simulate. Level sets describe the geometry in a nonparametric way so that geometrical and topological changes due to physics and in particular shed ice pieces are straight forward to follow. The model results are verified against the case of a free falling sphere. The capabilities of the proposed model are demonstrated on ice trajectories calculations for flow around iced cylinder and airfoil.